2005
DOI: 10.1177/1363461505058921
|View full text |Cite
|
Sign up to set email alerts
|

Religious Practice and Psychological Distress: The Importance of Gender, Ethnicity and Immigrant Status

Abstract: The present study examined the relationship between religious practice and psychological distress in a culturally diverse urban population to explore how religious affiliation, gender, ethnicity, and immigrant status affect this relationship. Data were drawn from a study of health care utilization in Montreal. A stratified community sample of 1485 yielded four religious groups: Protestant (n = 205), Catholic (813), Jewish (201), and Buddhist (150), and a group with no declared religion (116). The sample was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 34 publications
2
31
1
4
Order By: Relevance
“…This analysis indicated that certain groups were more vulnerable to high psychological distress: women, older people, the divorced/widowed, the secular, those who had less than college education, the unemployed and particularly those in the 'not in workforce' category. In all these groups, the scores for psychological distress were higher for immigrants [59], employment [19,53], and religious observance [72]. The present findings, however, differ from previous studies in three respects.…”
Section: Discussioncontrasting
confidence: 99%
“…This analysis indicated that certain groups were more vulnerable to high psychological distress: women, older people, the divorced/widowed, the secular, those who had less than college education, the unemployed and particularly those in the 'not in workforce' category. In all these groups, the scores for psychological distress were higher for immigrants [59], employment [19,53], and religious observance [72]. The present findings, however, differ from previous studies in three respects.…”
Section: Discussioncontrasting
confidence: 99%
“…The socialization of young Latino children in U.S. schools could be related to family cultural conflict, which itself may have an impact on the social support network. On the other hand, religious attendance, common among low-income Latino groups, might help minorities cope with the hardship of disadvantageous circumstances (Jarvis, Kirmayer, Weinfeld, & Lasry, 2005) by establishing socially-protective ties that buffer stressors.…”
Section: Immigration Factors and Family Stressors And Supportsmentioning
confidence: 99%
“…De manière générale, le lien entre le sens accordé à la détresse et les ressources mobilisées par les immigrants en pré-sence de celle-ci demeure un objet d'étude négligé. Les recherches ayant tenté de saisir le sens associé aux différents itinéraires thérapeutiques utilisés par les migrants au Canada ont mis en évidence plusieurs aspects dépas-sant grandement le seul domaine psychomédical (Horne et al 2004;Jarvis et al 2005;Whitley et al 2006). Compte tenu de ces résultats, les chercheurs souhaitant rendre compte des attitudes des populations immigrantes en termes de santé mentale se doivent de s'intéresser aux « réseaux à travers lesquels les acteurs transforment des valeurs uniques en pratiques » [ma traduction] (Bibeau 1997 : 249).…”
Section: Introductionunclassified